Arriving at comprehension (2011)
The path to understanding is a different path in each particular situation. It can be long or short, straight or winding, fast or slow. It can be continuous or interrupted. There are no formulas or recipes that are valid for everyone, not even for the same person. What can be generalized is that everyone must go through it in order to reach what, otherwise, is always a transitory place. Never definitive.